2012
DOI: 10.5650/jos.61.433
|View full text |Cite
|
Sign up to set email alerts
|

Jacaric Acid, a Linolenic Acid Isomer with a Conjugated Triene System, Reduces Stearoyl-CoA Desaturase Expression in Liver of Mice

Abstract: INTRODUCTION Among fatty acids with conjugated double bonds, the best known is conjugated linoleic acid (CLA) , a geometric and positional isomer of linoleic acid. CLA has various beneficial effects, including anticarcinogenic, antiobesity and antiallergic properties 1-5). Seed oils from certain plants also include conjugated linolenic acids (CLnAs) , which have a conjugated triene system and are geometrical and positional isomers of α-linolenic acid (LnA, 9c, 12c, 15c-18:3) 6-8) .We have performed several stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 28 publications
(22 reference statements)
5
24
0
Order By: Relevance
“…Previous studies showed that exogenous oleic acid or palmitoleic acid completely abrogated the action of t10, c12-CLA 11,18 . Interestingly, dietary jacaranda seed oil decreased the delta-9 desaturation index in the liver and adipose tissue and showed inhibitory effects on SCD-1 mRNA expression in the liver of ICR mice 19 . As already described, JFA contains 11.1 oleic acid; however, the cytotoxic effect of JFA was not inferior than that of pure JA.…”
Section: Figmentioning
confidence: 99%
“…Previous studies showed that exogenous oleic acid or palmitoleic acid completely abrogated the action of t10, c12-CLA 11,18 . Interestingly, dietary jacaranda seed oil decreased the delta-9 desaturation index in the liver and adipose tissue and showed inhibitory effects on SCD-1 mRNA expression in the liver of ICR mice 19 . As already described, JFA contains 11.1 oleic acid; however, the cytotoxic effect of JFA was not inferior than that of pure JA.…”
Section: Figmentioning
confidence: 99%
“…This has been observed with jacaric acid, which downregulated the expression of stearoyl-CoA desaturase, a key enzyme in fatty acid metabolism, in the liver of mice [22]. When administered alone, ursolic acid increased the activity of the lipolytic enzymes in primary cultures of adipocytes [23], inhibited the predifferentiation of the preadipocytes, stimulated lipolysis in the 3T3-L1 cells [24], and, in this study, reduced the total body mass and WAT in vivo .…”
Section: Discussionmentioning
confidence: 88%
“…Dietary treatments (LnA, CLnA and CLA) of both experiments, caused decreased the amount of MUFA, whereas the PUFA level was increased in adipose tissue, the SFA level was unchanged. Shinohara et al analyzed fatty acid profile of different tissues of ICR mice fed jacardic acid. Authors reported that levels of MUFA in liver and white adipose tissue were also decreased.…”
Section: Discussionmentioning
confidence: 99%